Visual art experiences through touch using haptices - Riitta Lahtinen; Russ Palmer; Stina Ojala (Netherlands, 2026)
Dual-sensory impaired person's perception of visual art (paintings, photos, statues etc.) may differ to those who are sighted. In such cases approaches defined as environmental description can be used to enable experience of different art forms. Environmental description can be portrayed through touch. (Lahtinen, Palmer & Lahtinen, 2010.) Art elements are portrayed through haptices i.e. touch messages during interaction between two people. Haptices are formed by combining haptemes, i.e. they obey the grammar of touch. This originates from social-haptic communication (Lahtinen, 2008). In this article these grammatical elements of touch are analysed further, especially in connection with experience of perspective. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Professor Heikki Ruismaki and Adjunct professor Inkeri Ruokonen